FAKTOR-FAKTOR PENYEBAB KEGAGALAN BISNIS PADA PERUSAHAAN MITRA JAYA ABADI - Muhammad Yusri Ali; David Sukardi Kodrat (Universitas Ciputra Surabaya, 2017)
Mitra Jaya Abadi is a food manufacturing company that produces healthy cookies made from oatmeal, the product named Bite And Bites. Bite and Bites sold in online and offline. The journey ofMitra Jaya Abadi initially went smoothly, but the longer it goes, the more decrease the business turnover is. As a result, the company can not achieve the set targets and has declared a failure. The purpose of this study was to determine what factors are causing failure of his company,Mitra Jaya Abadi. The sources of data are determined by certain considerations, and the respondents are the owner of the company, and mentors who have guided the company a minimum of two semesters. The method used is descriptive qualitative method with semi-structured using interviews and documentation. Then the data are tested using the test validity and reliability. The results show that the factors that cause business failures in the company Mitra Jaya Abadiare factor of strategy and factor of communication within the company.